Pengembangan Media Pembelajaran Interaktif Pada Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VIII SMP Negeri 2 Muara Kaman - Riyadi, Husni (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2025)
This research aims to develop and determine the feasibility of interactive media in class VIII social studies subjects that can be used to support the learning process. The research method is Research and Development (R&D) with the ADDIE development model namely analysis, design, development, implementation and evaluation. This research was carried out from January to February 2024. While the object of the research was interactive powerpoint media. This data collection technique uses questionnaires and interviews which are analyzed descriptively. The results of this research are interactive learning media for class VIII social studies subjects (1) the results of validation by material experts are included in the assessment criteria